2003
DOI: 10.1016/s0960-9822(03)00381-6
|View full text |Cite
|
Sign up to set email alerts
|

Negative Feedback Regulation of FGF Signaling Levels by Pyst1/MKP3 in Chick Embryos

Abstract: Pyst1 is an inducible antagonist of FGF signaling in embryos and acts in a negative feedback loop to regulate the activity of MAPK. Our results demonstrate both the importance of MAPK signaling in neural induction and limb bud outgrowth and the critical role played by dual specificity MAP kinase phosphatases in regulating developmental outcomes in vertebrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
162
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(181 citation statements)
references
References 54 publications
19
162
0
Order By: Relevance
“…More specifically, Fgf3 and Fgf8 have pronounced expression in the pharyngeal endoderm and ectoderm, and embryos injected with antisense morpholinos directed against the transcripts of these two genes fail to form pharyngeal cartilages (David et al, 2002;Walshe and Mason, 2003). Other studies have also noted that the mature pharyngeal arches are a prominent site of expression of members of the FGF synexpression group, including the transcriptional effectors pea3 and erm, as well as inhibitors of FGF signaling, such as Pyst1 (MKP3) and sprouty 2 (Munchberg et al, 1999;Chambers and Mason, 2000;Chotteau-Lelievre et al, 2001;Eblaghie et al, 2003;Walshe and Mason, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, Fgf3 and Fgf8 have pronounced expression in the pharyngeal endoderm and ectoderm, and embryos injected with antisense morpholinos directed against the transcripts of these two genes fail to form pharyngeal cartilages (David et al, 2002;Walshe and Mason, 2003). Other studies have also noted that the mature pharyngeal arches are a prominent site of expression of members of the FGF synexpression group, including the transcriptional effectors pea3 and erm, as well as inhibitors of FGF signaling, such as Pyst1 (MKP3) and sprouty 2 (Munchberg et al, 1999;Chambers and Mason, 2000;Chotteau-Lelievre et al, 2001;Eblaghie et al, 2003;Walshe and Mason, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…1E,F). To assess the impact on FGF signal reception, we assayed for the expression of genes regulated by FGFs, including sprouty (Spry) 2, Spry4 and Mkp3 (Dusp6 -Mouse Genome Informatics) (Eblaghie et al, 2003;Kawakami et al, 2003;Minowada et al, 1999). Their expression suggests that FGF signaling is markedly reduced, although not abolished, in the Tcre;Fgfr1 limb buds (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Third, using phosphorylated-ERK as an indicator of FGF signal activation, it has been shown that only cells in the distal mesenchyme of the limb bud are under the influence of FGF (Corson et al, 2003). This is confirmed by the expression patterns of Spry genes and Mkp3, which are transcriptionally regulated by FGF signaling (Eblaghie et al, 2003;Kawakami et al, 2003;Minowada et al, 1999). Consistent with our hypothesis, the expression pattern of Spry4 complements the observed cell death domain in normal limb buds (compare Fig.…”
Section: Fgfr1 Expressed In Lbm Is Essential For Cell Survivalmentioning
confidence: 94%
“…MKP-3 specifically binds to and inactivates ERK1 and 2, and recent studies indicate that this enzyme plays a pivotal role in regulating MAP kinase activity in response to fibroblast growth factor signaling during early development (6,41). MKPs exhibit distinct subcellular localization in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…To dissect the sequence requirements for this localization, we have expressed MKP-3 as an amino-terminal GFP fusion protein. This protein is fully active and able to dephosphorylate ERK2 when expressed in mammalian cells, indicating that MKP-3 is not folded abnormally when expressed as a fusion to GFP (6). Unlike GFP alone, which is distributed between the nucleus and the cytoplasm, MKP-3-GFP is predominantly cytoplasmic when expressed in both HeLa and NIH3T3 cells (Fig.…”
Section: Both Endogenous Mkp-3 and Mkp-3-gfp Are Cytoplasmicmentioning
confidence: 91%